Knowledge, Attitudes and Practices of Tailors towards the Business of COVID Masks and Protective Gears in Ghana. A Critical Literature Review - Bakker-Edoh , Dymphna; Opoku, Moses; Kassah, Johnson (International Journal of Fashion and Design, 2021)
Purpose: The study sought to investigate Knowledge, attitudes and practices of tailors towards the business of Covid masks and protective gears in Ghana. A critical Literature review. Methodology: This study adopted a desktop methodology. This study used secondary data from which include review of existing literature from already published studies and reports that was easily accessed through online journals and libraries. Findings: The study findings demonstrate a high level of awareness of COVID-19 among the tailors and general civilians who frequently updated themselves on the pandemic through several information channels. The pandemic disease, was broadcasted daily through all media, including social media and mainstream media (such as public television channels and radio). The study showed that the tailors also had heard about the need for more masks primarily through national TV channels which represented the primary source of information for remote communities in particular, and social media. Since the outbreak, many tailors have taken the opportunity to make custom-made masks. Unique Contribution to Theory, Practice and Policy: The results suggest an urgent need for health education programs to hold optimistic attitudes and rebuilding of trust of the general public in health facilities in local hospitals to avoid the possible next wave of COVID-19. The study also recommends that the government together with international donors should support local tailors by giving them funds to buy material they can use to make more protective gears.